Compliance with the U.S. Nuclear Regulatory Commission Revised Licensing Guidance for Radioactive Seed Localization. Issue 3 (September 2018) - Sheetz, Michael; Steiner, Cynthia
Abstract : Abstract: The use of radioactive seed localization (RSL) as a reliable alternative to wire localization (WL) for guiding the surgical excision of non-palpable lesions has become more popular because of its demonstrated advantages for both the patient and surgeon. RSL is regulated under 10 CFR 35.1000 (Other Medical Uses) for which the U.S. Nuclear Regulatory Commission (U.S. NRC) issued its original licensing guidance entitled "I-125 and Pd-103 Low Dose Rate Brachytherapy Seeds Used for Localization of Non-palpable Lesions" in 2006. At that time, RSL was performed as an off-label use of the same radioactive 125 I seeds used for brachytherapy, so the focus of this initial guidance was to establish the same requirements for RSL as for brachytherapy. Strict compliance with the licensing guidance was burdensome and made it difficult for some licensees to implement an RSL program. In response to a request from the user community and recommendations from an Advisory Committee on the Medical Use of Isotopes (ACMUI) subcommittee, the U.S. NRC formed a working group to consider revisions to its RSL guidance to make it more relevant to the conduct of the procedure. On October 7, 2016, the U.S. NRC issued a revised licensing guidance document titled "Low Activity Radioactive Seeds Used for Localization of Non-Palpable Lesions and Lymph Nodes." This manuscript highlights the changes in the latest U.S. NRC licensing guidance for RSL, including authorized user training and experience, written directives, surveys, instrumentation, and medical event criteria, and presents practical ways to satisfy the new requirements.